Cost-Effectiveness Analysis of Dimethyl Fumarate in the Treatment of Relapsing Remitting Multiple Sclerosis: An Italian Societal Perspective - Mantovani, Lorenzo Giovanni; Furneri, Gianluca; Bitonti, Rossella; Cortesi, Paolo; Puma, Elisa; Santoni, Laura; Prosperini, Luca (Farmeconomia. Health economics and therapeutic pathways, 2019)
BACKGROUND: Delayed-release dimethyl fumarate (also known as gastro-resistant dimethyl fumarate, hereafter dimethyl fumarate) is an oral disease-modifying therapy used for the treatment of Relapsing-Remitting Multiple Sclerosis (RRMS), an autoimmune chronic inflammatory condition of the central nervous system. OBJECTIVE: The objective of this economic analysis was to compare cost-effectiveness of dimethyl fumarate with the alternatives used as first-line treatment of RRMS in Italy. METHODS: The analysis was conducted from the Italian societal perspective. Health outcomes and costs were evaluated over a 50-year time horizon (equivalent to a lifetime horizon). Both health outcomes and costs were discounted at 3.5%. The cost-effectiveness analysis was conducted by adapting a Markov model, already used in previous similar economic analyses conducted in RRMS, to the Italian context. The Markov model estimated the clinical and economic consequences of treating RRMS patients with the following therapeutic options: dimethyl fumarate; interferon (IFN) beta-1a subcutaneous (SC) at two different doses, 22 mcg and 44 mcg; IFN beta-1b SC; glatiramer acetate (GA) SC 20 mg; oral teriflunomide. Clinical efficacy data were retrieved from an elaboration of an already published mixed treatment comparison (MTC). Both direct and indirect costs (disability, treatment acquisition, administration, monitoring, relapses, adverse events) were included in the analysis. One-way and probabilistic sensitivity analyses were carried out and cost-effectiveness acceptability curves generated. RESULTS: In the base-case analysis, dimethyl fumarate was more efficacious than alternatives, in terms of both survival (19.634 vs. 19.440-19.600 life years for alternatives), and quality-of-life-adjusted survival (6.526 vs. 5.143- 6.189 QALYs for alternatives). The total lifetime cost per patient treated with dimethyl fumarate (€ 954,286) was lower than that of the other DMTs included in the analysis. Therefore, dimethyl fumarate was dominant compared with all analyzed alternatives. Dimethyl fumarate was also the therapeutic option with the highest benefit on disease burden. In fact, costs of disability management were lower than those of all the other first-line drugs included in the analysis. The results of one-way deterministic sensitivity analysis and probabilistic sensitivity analysis confirmed the reliability of base-case results. CONCLUSIONS: The results of the cost-effectiveness analysis confirm that dimethyl fumarate is an optimal first-line treatment for RRMS in Italy, compared with the other first-line alternatives included in the economic analysis, when evaluated from the societal perspective.